2008
DOI: 10.2174/092986708783955527
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Gene Expression Profiling in Meningiomas and Schwannomas

Abstract: Microarray gene expression profiling is a high throughput system recently used in basic and applied research. It provides a large amount of data -at molecular level- that once acquired, must be functionally integrated in order to find common patterns within a defined group of biological samples. In addition to identification of differentially expressed genes and the establishment of gene regulation patterns, microarrays may also allow us to discover new tumor markers that could have a great impact on the impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 83 publications
0
17
0
Order By: Relevance
“…Microarray transcriptomic studies might be a useful complement to conventional diagnosis (70). Our data on the differential expression of gene transcripts in the three groups of meningiomas remain to be validated immunohistochemically when antibodies are available for proteins such as CKS2, UBE2C, GPX3, AOX1 and SERPINF1.…”
Section: ------------------------------------------------------------mentioning
confidence: 98%
“…Microarray transcriptomic studies might be a useful complement to conventional diagnosis (70). Our data on the differential expression of gene transcripts in the three groups of meningiomas remain to be validated immunohistochemically when antibodies are available for proteins such as CKS2, UBE2C, GPX3, AOX1 and SERPINF1.…”
Section: ------------------------------------------------------------mentioning
confidence: 98%
“…This gene encodes for the Protein 4.1B, located on chromosome 18p11.3. DAL1 gene is generally expressed at high levels in the brain and low levels in the kidney, intestine and testicles (Martinez-Glez, Franco-Hernandez et al 2008). DAL1 loss, together with reduced protein expression of its gene product was detected in sporadic meningiomas, affecting more than 70% of tumors regardless of histological grade (Gutmann, Donahoe et al 2000;Perry, Cai et al 2000).…”
Section: Dal1/41b a Member Of The 41 Protein Familymentioning
confidence: 99%
“…The low mutational frequency of this gene discounts sequence variations in DAL1 as the main mechanism underlying participation of this gene in the neoplastic transformation of meningiomas, and suggests that other inactivating mechanism, such as epigenetic changes, may participate in DAL1 silencing (Martinez-Glez, . Additional analyses have shown that DAL1 suppresses the growth and cellular proliferation in meningiomas by activating, among others, the Rac1-dependent c-Jun-NH(2)-kinase signaling pathway (Martinez-Glez, Franco-Hernandez et al 2008). However, the fact that transgenic mice lacking DAL1 do not develop tumors (Yi, McCarty et al 2005), suggests that DAL1 alterations may represent an early progression associated rather than an initiation event for the development of meningiomas.…”
Section: Dal1/41b a Member Of The 41 Protein Familymentioning
confidence: 99%
See 2 more Smart Citations